Effect of aggressive diuresis in acute heart failure with reduced and preserved ejection fraction - Xin He; Bin Dong; Ruicong Xue; Jingjing Zhao; Zexuan Wu; Yuzhong Wu; Yuanyuan Zhou; Dexi Wu; Yugang Dong; Jiangui He; Chen Liu (ESC Heart Failure, 2021)
Abstract Aims Heart failure with reduced ejection fraction (HFrEF) and heart failure with preserved ejection fraction (HFpEF) had distinct haemodynamic characteristics in the setting of acute heart failure. The aim of our study is to evaluate the differential response to aggressive diuresis in HFrEF and HFpEF. Methods and results Patients in the Diuretic Optimization Strategies Evaluation trial with left ventricular ejection fraction measurement were included (n = 300) and classified into HFrEF [left ventricular ejection fraction (LVEF) < 40%] (n = 193) and HFpEF (LVEF ≥ 40%) (n = 107). Effect of high‐dose vs. low‐dose furosemide strategy was compared separately in HFrEF and HFpEF. In HFrEF, high‐dose strategy did not increase change in creatinine or cystatin C at 72 h [treatment difference: −0.05, 95% confidence interval (CI): −0.14 to 0.03 mg/dL; P = 0.23 for creatinine, and treatment difference: −0.06, 95% CI: −0.15 to 0.02 mg/dL; P = 0.15 for cystatin C] compared with low‐dose strategy, but there were significantly more net fluid loss, weight loss, and congestion‐free patients at 72 h in high‐dose group. It was also associated with a significantly lower risk of composite clinical outcome of death, total hospitalizations, and unscheduled visits due to heart failure. In HFpEF, high‐dose strategy significantly increased change in creatinine and cystatin C at 72 h (treatment difference: 0.16; 95% CI: 0.02–0.30 mg/dL; P = 0.03 for creatinine, and treatment difference: 0.26; 95% CI: 0.09–0.43 mg/dL; P = 0.003 for cystatin C), but did not significantly affect net fluid loss, weight loss, proportion of congestion‐free patients at 72 h, and risk of the composite clinical outcome. Conclusions Acute heart failure on the basis of HFrEF and HFpEF responded differently to aggressive diuresis. Future trials should be designed separately for HFrEF and HFpEF.